Differential impact of target vessel on the diagnostic performance of resting full-cycle ratio as non-hyperemic physiological assessment. (25th November 2020) - Takashima, H; Ohashi, H; Ando, H; Suzuki, A; Sakurai, S; Nakano, Y; Sawada, H; Fujimoto, M; Naito, K; Tanabe, S; Suzuki, W; Waseda, K; et al.
Abstract: Background: Recently, wire-based resting indices have been recognized as gold standard for evaluating physiological lesion assessment. The resting full-cycle ratio (RFR) is a unique resting index which is calculated as the point of absolutely lowest distal pressure to aortic pressure during entire cardiac cycle. It is unclear whether the diagnostic performance of RFR for detecting functional coronary artery stenosis is similar in each coronary artery. The aim of this study is to compare the diagnostic performance of RFR based on target coronary vessel. Method: This study was a prospectively enrolled observational study. A total of 156 consecutive patients with 220 intermediate lesions were enrolled in this study. The RFR was measured after adequately waiting for stable condition, while FFR was measured after intravenous administration of ATP (180mcg/kg/min). Lesions with FFR ≤0.80 were considered functionally significant coronary artery stenosis. Results: In all lesions, reference diameter, diameter stenosis, lesion length, RFR, and FFR were 3.0±0.7mm, 45±13%, 13.0±8.8mm, 0.90±0.09, and 0.82±0.10, respectively. Functional significance was observed in 88 lesions (40%) of all lesions. RFR showed a significant correlation with FFR in overall lesions (r=0.774, p<0.001). The ROC curve analysis of RFR showed good accuracy for predicting functional significance (AUC 0.87, diagnostic accuracy 81%) in all subjects. Regarding each target vessel, there were similar and significant positive correlation between RFR and FFR (LAD; r=0.733, p<0.001, LCX; r=0.771, p<0.001, RCA; r=0.769, p<0.001, respectively). The prevalence of discordant between RFR and FFR was significantly different among 3 vessels (LAD 26%, LCX 12%, RCA 13%, respectively, p<0.05 for among 3 groups). Regarding the comparison of ROC curves according to lesion location, AUC was significantly lower in LAD than in LCX and RCA (LAD 0.780, LCX 0.947, RCA 0.926, p<0.01 for LAD compared to LCX, p<0.01 for LAD compared to RCA, respectively). Furthermore, the diagnostic accuracy was significantly different according to target vessel (LAD 74%, LCX 88%, RCA 87%, respectively, p<0.05 for among 3 vessels). Conclusion: RFR demonstrated better diagnostic accuracy for evaluating functional lesion severity. The diagnostic performance of RFR was different based on target vessel. RFR is a unique and useful resting index, and it may detect functionally significant coronary stenosis that cannot be detected with other resting indices in daily practice. Funding Acknowledgement: Type of funding source: None